ChemInform Abstract: Biomedical Applications of DNA‐Nanomaterials Based on Metallic Nanoparticles and DNA Self‐Assembled Nanostructures. Issue 20 (April 2016) - Wen, Yanli; Li, Lanying; Wang, Lele; Xu, Li; Liang, Wen; Ren, Suzhen; Liu, Gang
Abstract: Review: [67 refs.